Jieduquyuziyin Prescription-Treated Rat Serum Suppresses Activation of Peritoneal Macrophages in MRL/Lpr Lupus Mice by Inhibiting IRAK1 Signaling Pathway. (3rd November 2019) - Ji, Lina; Hou, Xiaoli; Deng, Xian; Fan, Xuemin; Zhuang, Aiwen; Zhang, Xiufeng; Li, Rongqun
Abstract : Systemic lupus erythematosus (SLE) is a chronic autoimmune disease, and Jieduquyuziyin prescription (JP) is a traditional Chinese medicine (TCM) formula that has been testified to be effective for SLE treatment as an approved hospital prescription for many years in China. However, its mechanism of action in the treatment of this disease is largely unknown. The purpose of this study was to determine whether JP-treated rat serum can inhibit the activation of peritoneal macrophages in MRL/lpr mice by downregulating the IRAK1 signaling pathway, thereby achieving the effect of improving SLE. The JP-treated rat serum was prepared, and the peritoneal macrophages of MRL/lpr lupus mice were isolated in vitro, and the effect of JP on cell viability was detected by the CCK8 method. After LPS induction and shRNA lentiviral transfection, the effect of JP on the expression of IRAK1 in cells was detected by immunofluorescence staining. The content of TNF- α and IL-6 in the cell supernatant was determined by ELISA. The expression of IRAK1, NF- κ B, TNF- α, and IL-6 mRNA was detected by RT-PCR, and the expression levels of IRAK1, p-IRAK1, TRAF6, IKB α, p-IKB α, IKK + IKK, NF- κ B, and p-NF- κ B proteins was detected by western blot method. We investigated the role of JP in peritoneal macrophages of the MRL/lpr mouse and identified the possible mechanisms of action. The results showed that JP could reduce the phosphorylation of IRAK1 and its downstream proteins induced by LPS and inhibit the expression of inflammatory cytokines, including TNF- α and IL-6. In addition, after the transfection of cells with shRNA lentiviral, the results of JP tended to be consistent. In conclusion, JP may inhibit the activation of peritoneal macrophages in MRL/lpr mice by downregulating the IRAK1-NF- κ B signaling pathway, and IRAK1 may be a potential target for JP treatment of SLE.